PENERAPAN MODEL PEMBELAJARAN CARD SORT PADA MATERI UNSUR GOLONGAN UTAMA - Zulfadli, Zulfadli; Hanum, Latifah; Muazzah, Muazzah (UIN AR-RANIRY, 2024)
Students' learning challenges brought on by an inadequate learning process served as the inspiration for this study. Students struggle to categorize alkaline, alkaline earth, halogen, and noble gas elements as a result. The activities, learning outcomes, and student reactions to the card sort learning model on the main group elements content are all intended to be described in this study. Descriptive study using a qualitative approach is the methodology employed. 21 students from SMAN 1 Krueng Barona Jaya's class XII MIA-2 chosen as the research subjects. Student activity observation sheets, test question sheets, and student answer questionnaires were the tools utilized in this study. Observing student activities in the first, second, third, and fourth meetings yielded results that fell into the good category: 71.02%, 75%, 78.26%, and 83.65%, respectively. 76.19% of students on average demonstrated competence of the learning goals. Eighty-three percent of students responded favorably to instruction utilizing the card sort learning model. Based on the study's findings, it can be said that using the card sort learning model with the primary group elements content can engage students in the learning process and help them master the subject matter. Additionally, students responded favorably to the use of the card sort learning model.